The Impact of Triangle Hierarchical Management on Self-Management Behavior and Quality of Survival in Parkinson's Patients - Yahua Zeng; Jianghua Huang; Xuan Tang; Ting Wang; Shuangqin Chen (Frontiers in Surgery, 2022)
ObjectiveTo investigate the effect of Triangle tiered and graded management on the self-management behavior and quality of survival of Parkinson's Disease (PD) patients.MethodsEighty ambulatory PD patients admitted to the neurology outpatient clinic of our hospital from June 2020 to January 2021 were selected for the study. Eighty patients were divided into 40 cases each in the test group and the control group using the random number table method. Patients in the control group were given conventional treatment and care, while in the test group, Triangle hierarchical management was applied on the basis of the control group. Non-motor symptoms [assessed by the Montreal Cognitive Inventory (MoCA), the Scale for Outcomes in PD for Autonomic Symptoms disability Scale (SCOPA-DS) and the Nocturnal Scale (SCOPA-NS)], motor symptoms [assessed by the Functional Gait Assessment (FGA), the Modified Ashworth Scale, and the Unified Parkinson's Disease Rating Scale (UPDRS-III)], quality of life (assessed by Barthel Index), medication adherence (self-administered medication adherence questionnaire), quality of survival (assessed by the 39-item Parkinson's Disease Quality of Survival Questionnaire, PDQ-39), and self-management effectiveness (assessed by the Chronic Disease Self-Efficacy Scale, symptom management and disease co-management) were compared between the two groups before and after the intervention. The two groups were also observed for satisfaction with care.ResultsAfter the intervention, the MoCA score, FGA score, Barthel Index, Medication adherence and all scores of self-management effectiveness were significantly higher in the test group than in the control group (P < 0.05); the SCOPA-DS score, SCOPA-NS score, Ashworth score, UPDRS-III score and PDQ-39 score were significantly lower than in the control group (P < 0.05). Satisfaction with nursing care was significantly higher in the test group than in the control group (P < 0.05).ConclusionThe application of Triangle's tiered and graded management to the home care of ambulatory PD patients was effective in improving their non-motor and motor symptoms, their ability to perform daily activities, medication adherence and self-management effectiveness, and their overall survival outcome.